Chromatin remodeling in oligodendrogenesis - E. V. Antontseva; N. P. Bondar (Вавиловский журнал генетики и селекции)
Oligodendrocytes are one type of glial cells responsible for myelination and providing trophic support for axons in the central nervous system of vertebrates. Thanks to myelin, the speed of electrical-signal conduction increases several hundred-fold because myelin serves as a kind of electrical insulator of nerve f ibers and allows for quick saltatory conduction of action potentials through Ranvier nodes, which are devoid of myelin. Given that different parts of the central nervous system are myelinated at different stages of development and most regions contain both myelinated and unmyelinated axons, it is obvious that very precise mechanisms must exist to control the myelination of individual axons. As they go through the stages of specification and differentiation – from multipotent neuronal cells in the ventricular zone of the neural tube to mature myelinating oligodendrocytes as well as during migration along blood vessels to their destination – cells undergo dramatic changes in the pattern of gene expression. These changes require precisely spatially and temporally coordinated interactions of various transcription factors and epigenetic events that determine the regulatory landscape of chromatin. Chromatin remodeling substantially affects transcriptional activity of genes. The main component of chromatin is the nucleosome, which, in addition to the structural function, performs a regulatory one and serves as a general repressor of genes. Changes in the type, position, and local density of nucleosomes require the action of specialized ATP-dependent chromatin-remodeling complexes, which use the energy of ATP hydrolysis for their activity. Mutations in the genes encoding proteins of the remodeling complexes are often accompanied by serious disorders at early stages of embryogenesis and are frequently identified in various cancers. According to the domain arrangement of the ATP-hydrolyzing subunit, most of the identified ATP-dependent chromatin-remodeling complexes are classified into four subfamilies: SWI/SNF, CHD, INO80/SWR, and ISWI. In this review, we discuss the roles of these subunits of the different subfamilies at different stages of oligodendrogenesis.